Prevalence and Comparative Analysis of Depression, Stress, and Anxiety Among Higher Secondary Students in Ukhrul Town, Manipur - Kashung, Thuishim (JOURNAL OF INDIAN EDUCATION, 2026)
Adolescence is characterised by significant physical, psychological, and emotional changes that heighten susceptibility to mental health disorders, including sadness, anxiety, and stress. This is particularly apparent in rural areas such as Ukhrul town, Manipur. This study sought to ascertain the prevalence of these psychiatric problems and to compare them between Grade 11 and Grade 12 higher secondary pupils. A descriptive survey methodology was employed utilising the standardised Depression Anxiety Stress Scale (DASS-42), with a stratified random sample of 300 adolescents from five schools. Data were examined using chi-square testing and percentage analysis. Results indicated that 71 per cent of students encountered sadness, 63.3 per cent experienced stress, and 79.3 per cent suffered from anxiety. Grade 12 pupils exhibited elevated levels of despair and stress compared to Grade 11 students. The research underscores the necessity for schoolbased mental health interventions, early detection systems, and awareness programmes specifically designed for the adolescent demographic in Ukhrul.